Investigating the Effect of Low-frequency Noise on Cognitive Performance and Physiological Responses: An Experimental Study - Siavash Etemadinezhad; Jamshid Yazdani Charati; Seyed Ehsan Samaei; Sedighe Jafarimanesh; Solale Ramezani (Mazandaran University of Medical Sciences, 2024)
Introduction and purpose: Noise is one of the most harmful physical factors in workplaces in both developed and developing countries. Still, low-frequency noise has not received enough attention, and the current regulations on its control are inadequate. To address this issue, the present study was conducted to examine the physiological response and cognitive functions of individuals before and after exposure to low-frequency noise. Methods: This study was conducted in the solar year 1401 and involved 40 students from Mazandaran University of Medical Sciences. Low-frequency noise with a level of 65 dB A was played for one hour. The patients' heart rates, blood pressure, and core temperatures were collected before and after exposure to low-frequency noise. Moreover, the continuous performance test was used to examine their cognitive performance. The data was analyzed using the Friedman and Voilcoxon tests in SPSS 25 software. Results: Low-frequency noise adversely impacted individual cognitive performance, increasing response error, omission error, and reaction time. However, according to the Wilcoxon test, only the increase in reaction time was statistically significant (P<0.05). Additionally, there was no significant difference in the individual's physiological indicators before and after exposure (P>0.05). Conclusion: Exposure to low-frequency noise generates greater discomfort than background noise with the same intensity level and has adverse effects on the individual's performance. Thus, the adverse effects of low-frequency noise are particularly significant in workstations that require mental processing of information and specific attention, such as control rooms and offices.